Biology education research in Turkey: Trends from 1989 to 2015 - Derman, Mustafa (Journal of Turkish Science Education, 2017)
This study was conducted to reveal out which biology subjects were preferred the most in Turkey in postgraduate theses; and to make comparisons of the university biology education, the types of publications, the research methods and investigated subjects. It was also aimed to find out the intensity of biology subjects dealt with in primary school and secondary school curriculum with regards to course hours on the basis of both the grades and the biology subjects. The qualitative research method was used in this study. The content analysis was used in data analysis. The result of study showed that; before 2000, MS theses were mostly done and PhD theses were fewer. Secondary school level was mostly preferred as for the research group and the “Quantitative” method was mostly preferred as for the research method. In addition, it was revealed out that; the environment, cell and variety of the living beings were among the topics that were studied the most in researches while the tissues, evolution, systems and energy were studied the least.